2013
DOI: 10.1590/0103-6440201301960
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Pretreatments on the Microtensile Bond Strength of Lithium-Disilicate Ceramic Repaired with Composite Resin

Abstract: The aim of this study was to evaluate the influence of ceramic surface treatments and silane drying temperature on the microtensile bond strength (μTBS) of a resin composite to a lithium disilicate ceramic. Twenty blocks (7x7x5 mm) of lithium disilicate-based hotpressed ceramic were fabricated and randomly divided into 4 groups: G1: acid etching with 9.5% hydrofluoric acid for 20 s and drying silane with room-temperature air; G2: acid etching with 9.5% hydrofluoric acid for 20 s and drying silane with 45 ± 5 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 21 publications
6
32
0
2
Order By: Relevance
“…Additionally, it was observed that the success of surface treatment depends on the ceramic type. For the lithium disilicate-reinforced glass ceramic, the etching with hydrofluoric acid promoted the highest µTBS values, which is in agreement with Colares et al (10). This ceramic has the lowest vitreous proportion among the ceramics tested in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, it was observed that the success of surface treatment depends on the ceramic type. For the lithium disilicate-reinforced glass ceramic, the etching with hydrofluoric acid promoted the highest µTBS values, which is in agreement with Colares et al (10). This ceramic has the lowest vitreous proportion among the ceramics tested in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Bonding components are also required for the adhesion to restorative material. Traditionally, surface treatment for ceramics involves roughening with diamond burs (7)(8)(9), etching with hydrofluoric acid (8,(10)(11)(12) or tribochemical process based on silica-coated aluminumoxide particles (11)(12)(13)(14)(15)(16)(17). For restorative material bonding, use of silane is recommended for glasses and porcelains in order to obtain a mesh of siloxane with the silica on the ceramic surface, to improve the bond strength between the ceramic and luting material and to increase the surface energy for adhesive application (18).…”
Section: Introductionmentioning
confidence: 99%
“…Bonding components are also required for the adhesion to a restorative material 18. Roughening with diamond burs,19 etching with hydrofluoric acid,2021 and sandblasting21 are the surface treatments recommended for ceramics. Silane is also used for ceramics in order to strengthen the bond between the ceramic and cement.…”
Section: Introductionmentioning
confidence: 99%
“…It can increase the surface energy for adhesive application 22. Although the intraoral repair process for ceramic restorations has been widely investigated in the literature,182123242526 limited information is available on the surface treatments and intraoral repair protocol for CAD/CAM resin-ceramic hybrid materials 1327. The aim of this in-vitro study is to evaluate the effect of surface treatments on SBS of resin composite bonded to thermocycled and non-thermocycled CAD/CAM resin-ceramic hybrid materials and to determine the effect of surface treatments on the surface roughness of these hybrid ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Surface treatments such as sandblasting and acid etching alter the surface topography by creating micro-and nano-scale porosities of varying depth and width 32) . The resultantaltered surface topography increases the surface area for micromechanical bonding with resin cements [33][34][35] . In the majority of the studies carried out, the effect of different numbers of firing and pressing on the color, surface roughness, hardness and microstructure of LDCs has been examined.…”
Section: Introductionmentioning
confidence: 99%